CORAL CÊNICO UFVJM: UM ESPAÇO DE ARTE E FORMAÇÃO ACADÊMICA - Madureira, José RAFAEL (Universidade Federal de Viçosa, 2018)
The present work is an experience report of the project of university extension called "Coral Scenic UFVJM". We aim to offer the academic community a space for study and practice of choral singing with an emphasis on theatrical performance. The project welcomes students, technicians and teachers of the UFVJM, as well as members of the external community. We use an active methodology inspired on JaquesDalcroze's Eurythmics principles. Except for vocal training exercises, all process is conducted through body exercises and theatrical games, which significantly contributes to the development of musical skills, including vocal tuning and harmonic perception from the chorus. The project is only two years old and already has a substantial repertoire for two, three and four voices, musical pieces sung in Portuguese, English, Spanish, German and Zulu dialect, which reveals the inherent transnationality of musical education environments